Shaping Children’s Social Ethics in Female Migrant Families: Islamic Insights on Education and Gender within the SDGs Framework - Nahrul Faidin; Tri Marhaeni Pudji Astuti; Sucihatiningsih Dian Wisika Prajanti; Puji Hardati; Alwy Ahmed Mohamed (Universitas Muhammadiyah Surakarta, 2025)
Objective: This study explores strategies for shaping children’s social ethics within female migrant families through the lens of Islamic values and the Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education) and SDG 5 (Gender Equality). Theoretical framework: The theoretical framework integrates the concepts of social behavior formation in families, character education theory (especially honesty and modeling), and religious education theory in the family context. This is reinforced by the Analytical Hierarchy Process (AHP) to determine strategic priorities in an objective and data-driven manner. Literature review: Literature review findings indicate that female migrant workers, despite limited physical presence, still play a pivotal role in shaping their children’s social ethics through intentional education, values transmission, and exemplary behavior. Prior research emphasizes family-based value education and identifies the need for measurable strategic frameworks such as AHP in prioritizing parenting methods. Methods: This research employs a qualitative descriptive approach using purposive sampling. Data were gathered through interviews, observation, document analysis, and structured questionnaires. Analytical Hierarchy Process (AHP), supported by Expert Choice 11 software, was used to prioritize educational strategies based on expert judgments. Results: The results identified three priority strategies: religious education (42.1%)—with emphasis on daily religious values (47.5%); exemplary behavior (43.5%)—highlighting the importance of parents as role models; and honesty education—prioritizing the alignment between words and actions (46.9%). The results were confirmed by a low inconsistency index (0.01), validating the reliability of the findings. Implications: The implications highlight the importance of reinforcing Islamic values in children’s social development, especially in the context of parental absence due to migration. The study provides guidance for mothers and educators to implement practical, measurable, and value-based approaches aligned with Islamic teachings and the SDGs. Novelty: The novelty lies in applying AHP to evaluate parenting strategies in migrant contexts—a method rarely used in character education research.